PENGARUH MODEL LATIHAN KIDS TSU CHU TERHADAP KETERAMPILAN BERMAIN SEPAKBOLA CLUB PUTRA MAYANA KU-20 KADUGEDE - Boby Agustan; Dany Ahmad Prasetyo; Ramdhani Rahman (Journal of Physical Education and Sport Science, 2022)
ABSTRACT Dany Ahmad Prasetyo (NIM: 182223031), with the title "INFLUENCE OF KID TSU CHU'S TRAINING MODEL ON THE SKILLS OF PLAYING CLUB PUTRA MAYANA KU-20 KADUGEDE". The purpose of this study was to determine the effect of training using the Kids Tsu Chu training model on the soccer playing skills of soccer players at Club Putra Mayana KU-20 Kadugede. This research method uses an experiment with a One-Group Pretest-Posttest research design with a population and a sample of 20 players of Club Putra Mayana KU-20 Kadugede, with a sampling technique using total sampling so as to obtain a sample of 20 people. The research method uses quantitative research methods. , the normality test of this data uses the Shapiro Whilk test with a significant value for the pretest and posttest data of 0.857 and 0.297 greater than 0.05 then the data is normally distributed. The significant value for the static lever is 0.646 > 0.05, then it is normally distributed. Furthermore, the value of Tcount obtained is -4.611 and for Ttable is 1.72913. because the value of Tcount > Ttable, it can be concluded that there is an effect of training using the Kids Tsu Chu training model on the soccer playing skills of Club Putra Mayana KU-20 Kadugede. Keywords: Kids tsu chu, Playing skills, Football